Reduction in 90 day readmission rates utilizing ambulatory pulmonary pressure monitoring. (27th November 2022) - Valika, Ali; Sulemanjee, Nasir; Pedersen, Rachel; Heidenreich, Debra
Abstract: Aims: In the CHAMPION (CardioMEMS Heart Sensor Allows Monitoring of Pressure to Improve Outcomes in New York Heart Association Functional Class III Heart Failure Patients) trial, heart failure hospitalization (HFH) rates were lower in patients with ambulatory pulmonary artery pressure (PAP) monitoring guidance. We investigated the effect of ambulatory haemodynamic monitoring on 90 day readmission rates after HFH. Methods and results: We retrospectively analysed patients across the Advocate Aurora Health hospital network who had undergone PAP sensor implantation between 1 October 2015 and 31 October 2019. Patients with a ventricular assist device (VAD) or transplant prior to implantation were excluded. Rates of total HFH and 30 and 90 day all‐cause readmission up to 12 months after implantation were collected, while censoring for an endpoint of heart transplantation, VAD, or death. Event rates were compared using Poisson regression. Of 459 patients included, there were 404 HFHs before and 179 after implantation. Compared with pre‐implantation, 30 day all‐cause readmission [incidence rate ratio (IRR): 0.55 (0.39–0.77), P = 0.0006] and 90 day all cause readmission rates were lower post‐implantation [IRR: 0.45 (0.35–0.58), P < 0.0001]. The effect of PAP sensor implantation on 90 day all‐cause readmission incidence rates was consistent across multiple subgroups. Conclusions: Across a large hospital network, ambulatory haemodynamic monitoring was associated with lower HFH rates, as well as 30 and 90 day all‐cause readmission rates. This supports the utility of ambulatory PAP monitoring to improve HF management in the era of value‐based medicine.